2022
DOI: 10.1038/s41586-022-04865-0
|View full text |Cite
|
Sign up to set email alerts
|

Limited cross-variant immunity from SARS-CoV-2 Omicron without vaccination

Abstract: SARS-CoV-2 Delta and Omicron are globally relevant variants of concern. Although individuals infected with Delta are at risk of developing severe lung disease, infection with Omicron often causes milder symptoms, especially in vaccinated individuals1,2. The question arises of whether widespread Omicron infections could lead to future cross-variant protection, accelerating the end of the pandemic. Here we show that without vaccination, infection with Omicron induces a limited humoral immune response in mice and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
126
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 26 publications
31
126
6
Order By: Relevance
“…The ability of Delta-elicited sera to cross-neutralize Omicron BA.1 is debated [ 48 , 49 , 68 , 80 , 91 , 92 , 93 , 94 , 117 ]. Our results clearly indicate that Gamma- or Delta-breakthrough sera with a high neutralizing activity against these VOCs are able to cross-neutralize Omicron BA.1, in agreement with previous studies [ 49 , 93 , 94 , 118 ], although our data only apply to vaccinated BTI infected with Delta and we cannot infer whether they extend to BTIs infected with other VOCs. Since breakthrough infection acts as a booster, this observation is congruent with the restoration of neutralizing ability induced by booster vaccination [ 27 , 28 , 44 , 46 , 48 , 57 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Discussionsupporting
confidence: 92%
“…The ability of Delta-elicited sera to cross-neutralize Omicron BA.1 is debated [ 48 , 49 , 68 , 80 , 91 , 92 , 93 , 94 , 117 ]. Our results clearly indicate that Gamma- or Delta-breakthrough sera with a high neutralizing activity against these VOCs are able to cross-neutralize Omicron BA.1, in agreement with previous studies [ 49 , 93 , 94 , 118 ], although our data only apply to vaccinated BTI infected with Delta and we cannot infer whether they extend to BTIs infected with other VOCs. Since breakthrough infection acts as a booster, this observation is congruent with the restoration of neutralizing ability induced by booster vaccination [ 27 , 28 , 44 , 46 , 48 , 57 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, we found that the mice boosted with the Omicron S DNA vaccine also maintained relatively higher RBD binding antibody and neutralizing antibody responses against the Delta variant. Our finding is consistence with most recent studies showing that Omicron infection alone did not induce superior cross-reactive antibody responses, while Omicron infection in previously vaccinated individuals can significantly enhance cross-protective neutralizing antibody responses ( 23 , 37 ). These observations suggest that a booster of an Omicron-matched vaccine might help to boost broadly neutralizing antibody responses.…”
Section: Discussionsupporting
confidence: 91%
“…[3][4][5][6][7] Omicron and omicron subvariants continue to cause significant morbidity and mortality and re-infection with omicron or a subvariant is possible, especially in unvaccinated individuals. [8][9][10] Immunization with an mRNA-1273 50-µg booster dose increases neutralizing antibody responses against variants and booster doses enhance vaccine effectiveness against Covid-19. [11][12][13][14][15][16] Nonetheless, effectiveness of the currently authorized vaccines against omicron is decreased compared to other variants [17][18][19][20] and consequently, a second booster dose was authorized in the US for immunocompromised individuals and adults >50 years of age in the midst of omicron waves.…”
Section: Introductionmentioning
confidence: 99%